Critérios para o aumento do índice de eficiência nos sistemas de irrigação tipo pivô central - Schons, Ricardo Luis (2010)
This work proposes improve the study about the efficiency indicators development, to be use in irrigation equipment for pivot. At first, it sought to make some clarifications about the current state of the irrigations technical, and how the society perceives it. In relation to the discussion of the technical evaluation, it sought to deliberate about the design project, since it theoric reason, even the best way of implementation thereof, with the goal to add knowledge to the area. The pivot equipment also was reason for presentation, answering the goal to clarify the terms and innovations. The main question discussed in the thesis concerns the theoretical foundation and the discussion on the question around the pursuit of technical efficiency. To discuss the implementation of energy efficiency measures in irrigation systems for pivot, it began with the methodology used for the evaluation of these systems. Right after, were calculated the performance indicators, and suitable the equipments in a standard efficiency, so to encompass the conditions of the energy and agricultural performance of the irrigation. The evaluation nowadays used to irrigation systems, is mainly carried over the Application Efficiency, with the help of uniformity indicators and with the installed potency evaluation. With this idea of indicator, it has a same parameter to compare installed systems in different conditions; this data has bigger applicability to assessments that are performed on equipment. The indicators were applied in 39 irrigation systems for pivot, in two regions of Rio Grande do Sul: Cruz Alta and Santo Augusto Region. With most medium-sized equipment (40 to 100 ha), with gap geometric mean total of 47,4 meters. The incomes of motorpump set ranged from 58% to 81%, with maximum potential reduction of power equipment in the Region of Cruz Alta of 29,41cv, and in the Region of Santo Augusto of 31,32cv. It was possible to complete that, according to the standard Energy Efficiency, The Specific Consumption Standard for irrigation, proposed by Lima (2008), 72% of the facilities from Region of Cruz Alta are above the standard (8,68 kWh.mm-1.ha-1.100m-1), and in the Region of Santo Augusto 64,28% are with the Consumption above standard.